Technology and Innovation in Agriculture: The Azores Case Study - Silva, E. L.D.G.S.; Oliveira, C. M.M.; Mendes, A. B.; Guerra, H. M.G.F.O. (International Journal of Interactive Mobile Technologies (iJIM), 2017)
A growing population world might exceed its food supply in the future. Food availability needs an increasing agricultural productivity and production through technology and innovation. European concerns about innovation policies reflected on the Lisbon Agenda include the European program PROPRURAL+ for the Portuguese Azores Islands. The agricultural innovation in the Azores started with the Green Revolution, which increased agricultural production, using seeds, fertilizers, chemical products and agricultural equipment. But much more innovation is needed for the Azores to became a well-sustained and competitive European region in this economic sector. For example, concerning milk, the region is responsible for more than 30% of the national production. But, since the liberalization in EU imposed by the global markets, a crisis in the sector is installed. Dairy producers are now facing many difficulties in trying to enhance the profitability of their farms, by reducing costs and improving efficiency. A characterization of the Azorean agriculture, emphasizing the milk production sector is presented. The specificities and the potential of the region are discussed and some agricultural innovations with IoT technologies are pointed out.